Variasi jumlah dan panjang batang pengupas pada mesin pengupas buah pinang terhadap efisiensi pengupasan buah pinang kering - Iman Syahrizal; Daud Perdana (TURBO [Tulisan Riset Berbasis Online], 2021)
The process of peeling betel nuts can be done manually or using a machine. Peeling betel nuts using a machine is easier and faster than peeling them manually. This study aimed to test the performance of the dry betel nut peeler machine and to prove the effect of the number and length of peeling rods on the efficiency of the peeling. The method used in this study was a randomized design experimental method consisting of two factors, namely the number of peeling rods (12 rods; 18 rods; 24 rods) and the length of the peeling rods (1 cm; 1.5 cm; 2 cm) with nine test variations. . The parameters observed included percentage of unpeeled fruit, percentage of peeled fruit with broken seeds, and percentage of peeled fruit with unbroken seeds. The highest peeling efficiency was 88% at the interaction of the number of peeling rods of 18 pieces 1,5 cm long. The lowest stripping efficiency was 66% at the interaction of the number of peeling rods of 12, 2 cm long and the average stripping efficiency was 76%. The greater the number of peeling rods, the greater the percentage of peeled fruit. The longer the peeler rod, the greater the percentage of peeled fruit with broken seeds.Keywords: dry betel nut, peeler, efficiency.